1984
DOI: 10.1192/bjp.145.4.429
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Malignancy in Schizophrenia

Abstract: It has been suggested that schizophrenic patients have a lower risk of cancer than the general population. We therefore investigated the smoking patterns of 100 current chronic schizophrenic in-patients, and the causes of death in 122 recently deceased schizophrenics. We found that schizophrenics are heavy smokers, and that schizophrenics do die from carcinoma of the bronchus. Proportional mortality rates for all malignancies were not significantly lower in schizophrenics than in the general population but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
61
0
7

Year Published

1985
1985
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(72 citation statements)
references
References 12 publications
4
61
0
7
Order By: Relevance
“…These patients prefer high-nicotine content cigarettes and most frequently smoke the cigarette until the very end where nicotine concentration is higher. 13 It seems that studies investigating neurobiological relations between smoking and schizophrenia provide us with more robust evidence that could be replicated in similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…These patients prefer high-nicotine content cigarettes and most frequently smoke the cigarette until the very end where nicotine concentration is higher. 13 It seems that studies investigating neurobiological relations between smoking and schizophrenia provide us with more robust evidence that could be replicated in similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…In one study of institutionalized schizophrenic patients, authors found that 92% of the men and 82% of the women smoked. 16 It is generally documented that smoking, accompanied by beer or wine, further heralds the progression of dependence on other dangerous drugs like marijuana and opioids, 17 and is associated with a variety of serious medical disorders, including cancers. So it might not be surprising that nearly all patients were smoking cigarettes before artane abuse.…”
Section: Discussionmentioning
confidence: 99%
“…People with schizophrenia frequently smoke cigarettes and often smoke heavier than the normal population [9,10,11,12,13,14,15]. Additionally, they extract more nicotine from each cigarette they smoke presumably by deeper inhalation.…”
mentioning
confidence: 99%